Approaches in line with human physiology to prevent skin aging - Karimi, Nazli (Frontiers in Physiology, 2023)
Skin aging is a complex process that is influenced by intrinsic and extrinsic factors that impact the skin's protective functions and overall health. As the body's outermost layer, the skin plays a critical role in defending it against external threats, regulating body temperature, providing tactile sensation, and synthesizing vitamin D for bone health, immune function, and body homeostasis. However, as individuals age, the skin undergoes structural and functional changes, leading to impairments in these essential functions. In contemporary society, there is an increasing recognition of skin health as a significant indicator of overall well-being, resulting in a growing demand for anti-aging products and treatments. However, these products often have limitations in terms of safety, effective skin penetration, and potential systemic complications.To address these concerns, researchers are now focusing on approaches that are safer and better aligned with physiology of the skin.These approaches include adopting a proper diet and maintaining healthy lifestyle habits, the development of topical treatments that synchronize with the skin's circadian rhythm, utilizing endogenous antioxidant molecules, such as melatonin and natural products like polyphenols.Moreover, exploring alternative compounds for sun protection, such as natural ultraviolet (UV)absorbing compounds, can offer safer options for shielding the skin from harmful radiation.Researchers are currently exploring the potential of adipose-derived stem cells, cell-free blood cell secretome (BCS) and other endogenous compounds for maintaining skin health. These approaches are more secure and more effective alternatives which are in line with human physiology to tackle skin aging. By emphasizing these innovative strategies, it is possible to develop effective treatments that not only slow down the skin aging process but also align better with the natural physiology of the skin. This review will focus on recent research in this field, highlighting the potential of these treatments as being safer and more in line with the skin's physiology in order to combat the signs of aging.